Care of the soul a guide for cultivating depth and sacredness in everyday life - Moore, Thomas 1940-, Author (New York, NY HarperPerennial, 1994)
A therapist draws on the world's religions, music, art, and his own experiences with patients to examine the connections between spirituality and the problems of individuals and society.
I. Care of the soul -- 1. Honoring symptoms as a voice of the soul -- II. Care of the soul in everyday life -- 2. The myth of family and childhood -- 3. Self-love and its myth : narcissus and narcissism -- 4. Love's initiations -- 5. Jealousy and envy : healing poisons -- 6. The soul and power -- 7. Gifts of depression -- 8. The body's poetics of illness -- 9. The economics of soul : work, money, failure, and creativity -- III. Spiritual practice and psychological depth -- 10. The need for myth, ritual, and a spiritual life -- 11. Wedding spirituality and soul -- IV. Care of the world's soul -- 12. Beauty and the reanimation of things -- 13. The sacred arts of life.
"A hardcover edition of this book was published in 1992 by HarperCollins Publishers"--T.p. verso.
Includes bibliographical references (p. [311]-312).
Keywords: Spiritual life; Psychology, Religious